Analyzing entrepreneurship with the Finnish Linked Employer-Employee Data (FLEED): Matching and qualitative properties of the data - Mika Maliranta; Satu Nurmi (The Research Institute of the Finnish Economy (ETLA), 2004)
This paper explores the potential of the Finnish Longitudinal Employer-Employee Data (FLEED) in the analysis of entrepreneurship. It is found that these data are excellent for analyzing a certain sort of self-employed individuals who exercise their profession on their own account (elinkeinonharjoittajat). In these cases, where the company can be identified on the basis of the personal code of the self-employed, it is possible to see both sides of the self-employed, their individual characteristics and the properties their companies. On the other hand, the present data do not allow linking the limited liability companies to their owner entrepreneurs directly, which currently seriously limits the usefulness of the data for entrepreneurial analysis. Two possibilities to improve the situation are considered. Firstly, the self-employed can be matched to their companies by using background information of the self-employed and the companies. Our experiment shows, however, that relatively reliable matches can be found only for a rather small sample of the self-employed. A much more promising but more expensive option might be to use taxation registers on the ownership compiled by the taxation authorities. Linking individuals with companies on the basis of the ownership would open a great variety of interesting research opportunities. – Data ; self-employment ; entrepreneurs – – Tämä tutkimus selvittää suomalaisen yhdistetyn työantaja–työntekijä-aineiston (FLEED) käyttömahdollisuuksia yrittäjyystutkimuksessa. Aineisto näyttää soveltuvan erinomaisesti elinkeinoharjoittajien tutkimiseen, koska näissä tapauksissa yritykset identifioituvat suoraan yrittäjän oman henkilötunnuksen kanssa. Tällöin nähdään yrittäjän kaksi puolta; hänen henkilökohtaiset ominaisuutensa sekä hänen yrityksensä ominaisuudet. Toisaalta nykyinen aineisto ei anna mahdollisuutta yhdistää osakeyhtiömuotoisia yrityksiä niiden omistajayrittäjiin, mikä tällä hetkellä merkittävästi rajoittaa aineiston käytettävyyttä yrittäjätutkimuksessa. Tutkimuksessa selvitetään kahta vaihtoehtoista tapaa parantaa tilannetta. Ensiksi, yrittäjät voidaan yhdistää heidän yrityksiinsä käyttämällä hyväksi yrittäjien sekä yritysten taustatietoja. Kokeilumme kuitenkin paljastaa, että suhteellisen luotettavia yhdistämisiä kyetään tekemään vain melko pienelle yrittäjäjoukolle. Paljon lupaavampi, mutta kalliimpi vaihtoehto näyttäisi olevan verottajan kokoamien, yritysten omistusta koskevien rekisterien hyödyntäminen. Yksilöiden yhdistäminen yrityksiin omistajuuden perusteella tarjoaisi mahdollisuuksia moniin tutkimuskysymyksiin. – Data ; self-employment ; entrepreneurs
Keywords: L10; M13; 330; Selbstständige; Entrepreneurship-Ansatz; Finnland